ASSESSMENT OF THE PRESENCE OF ANHEDONIA DURING THE COVID-19 PANDEMIC IN STUDENTS OF THE FACULTY OF MEDICINE OF THE UNIVERSITY OF NIŠ - Malinić, Milan; Lakić, Jovana; Jovanović, Dunja; Simonović, Maja (Medicinski podmladak, 2024)
Introduction: Anhedonia is a psychopathological condition that is defined as the loss of the ability to experience pleasure. Describes the loss of a fundamental dimension of human experience. The Covid-19 pandemic created the conditions for the development of anhedonia, brought limitations, less positive experiences, limited planning, human contacts, limited movement and the constantly threatening danger of a bad outcome. The Aim: The aim of the study was to determine the state of anhedonia in the population of medical students during the Covid-19 pandemic and to determine whether there is a difference in the degree of anhedonia in the group of subjects suffering from Covid-19 infection compared to the group of subjects not suffering from Covid-19 infection. Material and Methods: The research was conducted using a questionnaire created on the Google platform (Google Forms). The link for the questionnaire was distributed via social media in the period January/February 2022. 191 students from the Medical Faculty of the University of Niš participated in the research. An assessment of the state of anhedonia was performed using the Snaith-Hamilton Pleasure Scale (SHAPS). The statistical significance of the differences between the groups was determined using the Student’s t-test. Results: Based on the obtained results, we conclude that the degree of anhedonia in the subjects is significantly low (score less than 2) for almost all dimensions of satisfaction, except for training, where a slight increase in anhedonia is observed (score is 2.13). Conclusion: The obtained results show that no indicators have been found that show the presence of anhedonia in the student population in the examined period of the Covid-19 pandemic. No differences in the state of anhedonia were found in the group of subjects who suffered from Covid-19 infection compared to students who did not suffer from Covid-19 infection.